Implementasi Usability Testing dalam Evaluasi Website Sekolah - Susan Dian Purnamasari; Firamon Syakti (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
One of the products of information technology that is common today is the school website. Where the school website is the spearhead for schools in disseminating information to related parties. The most important aspect of a website is the usability aspect because it greatly affects visitor convenience. The use of the website for disseminating information is also used by SMK Negeri Sumsel and the school's main portal on the internet. For that to see the importance of the usability aspect, this study aims to see the level of usability of the SMK Negeri Sumsel website. In measuring the level of usability, usability testing techniques are used with the stages of preparation, selecting respondents, data collection and data analysis. The test results show that the usability aspects on the website such as errors, learnability, memorability and satisfaction get good ratings while the efficiency aspects are not categorized as good.